The effect of lemongrass (Cymbopogon citratus) powder as a natural food preservatives for baye-baye. - Belascuain, Patricia A.
The effectiveness of lemongrass Cymbopogon citratus powder incorporated in baye-baye as a natural food preservative was tested in this study by evaluating the physico-chemical, microbiological properties and stability of samples incorporated with lemongrass powder and stored at ambient temperatures (28-34°C). Three formulations of baye-baye with 0%, 0.5% and 1.0% (w/w) concentrations of added lemongrass powder were analyzed. The analysis was done in three intervals, namely at 0 hour (Day 0), after 24 hours (Day 1), and after 48 hours (Day 2) of ambient storage conditions. Physico-chemical analyses on baye-baye with lemongrass powder had a pH ranges of 5.66 to 5.77 indicating samples to be low acid food, water activity range of 0.848 to 0.854, and moisture content range of 17.90% to 19.14%. Monitoring of baye-baye at ambient temperature was terminated after 48 hours of storage period upon the onset of rancidity producing off-odor. Stability test using free fatty acid determination resulted to 22.17% to 34.86% lauric acid for treated baye-baye compared to the control sample with range of 16.66% to 36.54% lauric acid. Total Plate Count of control and treated baye-baye, control baye-baye has a higher microbial load range from 7.55x104 to 7.08x106 CFU/g while the incorporation of lemongrass powder in baye-baye had a microbial load range of 4.07x104 to <1.41x106 CFU/g. Microbiological analysis of TPC showed that the microbial criterion based on the Center for Safety (2007) categorized the microbial count of baye-baye both the treated samples and the control sample to fall under unsatisfactory group. General acceptability of baye-baye incorporated with lemongrass powder was assessed using 9-point hedonic scale. The two formulations of baye-baye with lemongrass powder were preferred by the panelists having an average score rating of ?like moderately?. The distinct aroma of lemongrass obtained a possible result and contributed to the acceptability of the product. Throughout the storage period, increase in the total plate count and free fatty acid of the three formulations was observed although only pH and TPC showed significant differences throughout storage time. While the unsatisfactory rating of baye-baye suggests that there is the need to improve the method and practice in production of baye-baye and of application of other preservation techniques, the incorporation of lemongrass powder significantly contributed to the extension of shelf-life of baye-baye for two days.